A corpus-based study of authorial presence in the academic writing of Indonesian higher education EFL learners - Suhandoko, Suhandoko; Ningrum, Dian Riesti; Mustofa, Ali (Universitas Syiah Kuala, 2025)
Using appropriate stance markers is essential to enhance argumentation. However, scholars have consistently reported that linguistic, cultural, and instructional factors make developing persuasive skills in L2 writing instruction challenging. This quantitative study employed a corpus-based methodology to investigate the use of stance markers in the academic writing of Indonesian EFL learners to establish persuasive arguments. The dataset comprises academic essays from 59 learners who were part of their academic writing coursework. The stance markers were identified using AntConc software and analyzed following Hylands (2019) stance framework. The research revealed learners reliance on transitions to create a logical structure in their text, while the use of boosters slightly surpasses the use of hedges, reflecting their growing understanding of the need to balance certainty with caution in academic writing. The high frequency of markers for disagreement and doubt indicates their ability to engage effectively with alternative viewpoints. The findings of this study challenge the stigma that Asian EFL learners are less assertive in expressing their arguments and challenging opposing views because they adhere to their cultural communicative norms. However, we found the limited use of markers indicating subjectivity and evaluation, which points to a potential gap in pedagogical approaches and suggests the need for more targeted instruction to bridge culturally appropriate communication norms and academic writing conventions.